Identification of Methicillin-Resistant Staphylococcus aureus in poultry meat portions using Multiplex PCR - Jafarzadeh, Minoo; Meamar, Niloofar; Mohsenzadeh, Mohammad; Razmyar, Jamshid (Journal of Poultry Sciences and Avian Diseases, 2023)
Staphylococcus aureus is a prevalent bacterial colonizer with zoonotic potential, affecting humans and various animal species, including livestock, poultry, and pets. This study investigates methicillin-resistant S. aureus (MRSA) isolates in poultry meat portions using Multiplex PCR methods. A total of 210 samples, including 70 wings, 70 thighs, and 70 necks, were collected from Mashhad, Iran markets. S. aureus identification employed culture and phenotypical methods, while the disk diffusion method assessed antibiotic susceptibility using 14 different disks. The Multiplex PCR assay was developed to confirm S. aureus isolates and detect antibiotic resistance genes. Among the 210 samples, 52 (24.76%) tested positive for S. aureus. Antibiotic susceptibility testing revealed that 17 (32.69%) of the S. aureus isolates were resistant to methicillin. Tetracycline exhibited the highest resistance, followed by ampicillin (61.5%) and penicillin (57%). Conversely, chloramphenicol demonstrated the lowest resistance at 3.8%. All isolates were susceptible to gentamicin, vancomycin, imipenem, and ciprofloxacin. PCR analysis confirmed the presence of 16S rRNA and femA genes in all isolates, while 14 (26.92%) harbored the methicillin-resistant gene (mecA). The study suggests multiplex PCR is a valuable and sensitive technique for detecting antibiotic resistance genes in S. aureus within chicken meat, emphasizing its utility in surveillance and control efforts.